Ratiometric fluorescent strategy for malononitrile determination in organic and aqueous medium and biological imaging. (January 2021) - Gong, Yan; Guo, Xinjie; Teng, Baohui; Zhang, Qian; Zhang, Peng; Ding, Caifeng
Abstract: Malononitrile is a versatile dinitrile compound with high reactivity, which has wide prospect in application for multisynthetic organic medical chemistry and industrial manufacture. Considering of the transformation to HCN in animal tissue metabolism, malononitrile has potential environmental pollution and health risks. Here, a ratiometric fluorescent probe 4-(benzothiazol-2-yl)-2-hydroxy benzaldehyde (HBTA) for detection of malononitrile in organic and aqueous phase is developed on the basis of reaction-triggered fluorophore for the first time. The ratiometric assay with malononitrile-responsive fluorescence signal was contributed by Knoevenagel condensation and intramolecular cyclization, which was confirmed by HR-MS analysis and NMR titration spectra. In addition, this ratiometric probe provided a fancy strategy for detection of malononitrile with fast response, high sensitivity and selectivity, declaring excellent imaging performance in vivo capable of semi-quantification for malononitrile level. Graphical abstract: Image 1 Highlights: A ratiometric fluorescent strategy for malononitrile is developed for the first time. Knoevenagel condensation and intramolecular cyclization induced the sensing signal. The probe displays a sensitive response to malononitrile in organic/aqueous medium. The probe can be applied for intracellular and in vivo imaging for malononitrile.